2021
DOI: 10.1021/acs.est.1c04642
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Nitrite Production from the Aqueous Photolysis of Nitrate in the Presence of Vanillic Acid and Implications for the Roles of Light-Absorbing Organics

Abstract: A prominent source of hydroxyl radicals (•OH), nitrous acid (HONO) plays a key role in tropospheric chemistry. Apart from direct emission, HONO (or its conjugate base nitrite, NO2 –) can be formed secondarily in the atmosphere. Yet, how secondary HONO forms requires elucidation, especially for heterogeneous processes involving numerous organic compounds in atmospheric aerosols. We investigated nitrite production from aqueous photolysis of nitrate for a range of conditions (pH, organic compound, nitrate concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 84 publications
1
39
0
Order By: Relevance
“…128 Wang et al demonstrated the importance of solvated electrons produced from photosensitizing reactions in enhanced nitrite production from nitrate photolysis. 158 They suggested that the solvated electrons are mainly scavenged by nitrate, leading to more NO 2 production for further conversion to nitrite.…”
Section: Factors Affecting Particulate Nitrate Photolysismentioning
confidence: 99%
“…128 Wang et al demonstrated the importance of solvated electrons produced from photosensitizing reactions in enhanced nitrite production from nitrate photolysis. 158 They suggested that the solvated electrons are mainly scavenged by nitrate, leading to more NO 2 production for further conversion to nitrite.…”
Section: Factors Affecting Particulate Nitrate Photolysismentioning
confidence: 99%
“…, which could continue to react with H 2 O to form NO 2 reactions (12 and 13) (Wang, Huang, et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The large enhancement of P(HONO) (g) /[NO 3 ˉ] was probably because the complex organic compositions in snowmelt were much more efficient in enhancing HONO and O 2 • ˉ formation (Wang, Dalton, et al., 2020). A recent study has shown that brown carbon (BrC) may greatly enhance the NO 2 − production from the aqueous NO 3 − photolysis through photosensitizing reactions (Wang, Huang, et al., 2021). It has been shown that the triplet state of photosensitizer (P*) are sources of O 2 •− (Canonica et al., 1995).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On a related note, the significance of photosensitization by BrC (via formation of solvated electrons; Wang et al, 2021) and marine dissolved organic matter (via O 2 •formation; Garcia et al, 2021) in enhanced nitrite production from nitrate photolysis have been reported. A recent study from our group has shown that glyoxal photo-oxidation mediated by both nitrate photolysis and photosensitization can significantly enhance the atmospheric sink of glyoxal (Zhang et al, 2022).…”
Section: Conclusion and Atmospheric Implicationsmentioning
confidence: 97%